Short-and Long-Run Impact of Money Supply on Nepalese Stock Market Performance:Evidence from Johansen Co-integration, Vector Error Correction Model, and Granger Causality Analysis - Thapa, Krishna Bahadur (The Gaze: Journal of Tourism and Hospitality, 2024)
This study examines the short- and long-term effects of money supply (MS) on Nepalese stock market performance using monthly data from June 2005 to November 2023. Employing advanced econometric techniques—including Johansen co-integration, Vector Error Correction Models (VECM), and Granger causality tests are employed for the analysis of long-run co-integrating relationship and bidirectional causality tests between MS and the Nepalese stock performance. Augmented Dickey-Fuller (ADF) approach reveals non-stationary at first differences I (1) from various criteria. The Johansen co-integration test confirms a long-term relationship between the MS and the stock market performance at significance level. The VEC model reveals that past changes in MS have a statistically significant negative effect on current changes in the Index in the long run. The Wald test results show that the lagged values of the Index and MS do not jointly cause changes in the Index in the short run. The Granger causality test indicates a bidirectional causal relationship between MS and the Index, with both variables influencing each other.